Transformational Changes in the Lithuanian Economy: the Residential Real Estate Market and its Formation Premises - Kvedaravičienė, Ieva; Lydeka, Zigmas (Ekonomika, 1997)
While the formation of a market of production factors and a consumer market is often discussed in scientific literature, there is still not enough attention payed to the real estate market. The formation of an effective real estate market is conditioned by its high social importance, its infrastructual purpose, its validity of investing and consuming processes, and, finally, the successful functioning of the entire economy. The concept of real estate, socio-economical characteristics. and the specificity of the real estate market are analysed in this article. The largest and most active part of the Lithuanian real estate market is a residential one, so most attention in this article is focused on formation premises and development perspectives of this kind of real estate market. The residential real estate market can be classified into two relatively independent markets: • the primarly market, which consists of buildings which are now the process of construction (they have not yet been built or have just been built). Participants’ behaviour in this market is influenced by tbe general economic situation (rates of inflation, the volume of investment, purchaising power) and the size and pecularitie:s of the construction business. • the secondary market, which consists of earlier constructed buildings which arc now privatized by individuals and institutions. In some aspects, this market is intermediate: the participants have a starting capital-an old building or apartment - which can play the role of a starting investment in buying a new building (or apartment) in the primary market; therefore, the secondary market ensures a demand for residential real estate for residents who have a low income. The main parameters of the residential Teal estate market are the following: the demand for residential real estate and factors of its formation; the supply of residential real estate and factors of its formation. Residential real estate prices and their dynamics in primary and secondary markets arc also analysed and illustrated with statistical data. At the end of this article the main reasons it is worth white to invest in residential real estate, are given. Tendencies that can influence the Lithuanian residential real estate market’s socio-economical parameters in the future are also given.